The selection of philosophies and principles of the most prominent quality prophets and the integration thereof into the company's management and operational systems - Esterhuysen, Pieter Willem (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1987.